2003
DOI: 10.1016/s0741-5214(03)00416-6
|View full text |Cite
|
Sign up to set email alerts
|

Fabric tears as a new cause of type III endoleak with ancure endograft

Abstract: To our knowledge, these are the first type III endoleaks reported in association with Ancure endografts. Placement of Wallstents inside endografts is of concern, and another indication for close monitoring during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 17 publications
0
37
2
Order By: Relevance
“…7 Type III endoleak due to fabric defect is a rare but serious complication. It has been reported with other stent graft systems [8][9][10] and with the Zenith system in one case report in which the fabric tear was caused by balloon modeling during the implantation procedure. 11 No instance of late fabric disruption in a Zenith stent graft has previously been reported.…”
Section: Discussionmentioning
confidence: 87%
“…7 Type III endoleak due to fabric defect is a rare but serious complication. It has been reported with other stent graft systems [8][9][10] and with the Zenith system in one case report in which the fabric tear was caused by balloon modeling during the implantation procedure. 11 No instance of late fabric disruption in a Zenith stent graft has previously been reported.…”
Section: Discussionmentioning
confidence: 87%
“…8 In the case presented, the type III endoleak in the main device body was visualized after complete device deployment, leaving no possibility of withdrawing the endograft, and a narrow left iliac segment would not allow for deployment of a second bifurcated device body. To avoid open surgical repair, conversion to an aortomonoiliac design with femorofemoral crossover bypass was therefore chosen.…”
Section: Discussionmentioning
confidence: 81%
“…6 Transgraft (type III) endoleaks are caused either by disconnection of the components of a modular endograft system (IIIa) or by a direct defect in the stent-covering graft fabric (IIIb). 7,8 Large studies have reported incidence rates of type III endoleaks ranging from 0.7% to 7% after EVAR. [9][10][11] While it appears safe to observe branch vessel (type II) endoleaks unless the aneurysm enlarges, type III endoleaks, similar to attachment zone (type I) endoleaks, are strongly correlated with adverse events like aneurysm growth or rupture, and mandate reintervention.…”
Section: Introductionmentioning
confidence: 99%
“…5,9 Type III endoleaks should be treated promptly because direct endoleaks are associated with considerable risk of aneurysm rupture. [10][11][12] Treatment, which can be endovascular or open, is chosen according to anatomic features. In our case, treatment with an aorto-uni-iliac device (Zenith Renu; 32/115 mm) was chosen because it was felt that this was the easiest way to solve the problem.…”
Section: Discussionmentioning
confidence: 99%